Decoupled but not neutral: The effects of stochastic transfers on investment and incomes in rural Thailand - Andreas Wagener; Juliane Zenker (Leibniz Universität Hannover, Thailand Vietnam Socio Economic Panel (TVSEP), 2018)
In 2009, the Thai government implemented a price insurance scheme for rice farmers. The program, which was abandoned after only one year, added to the incomes of registered farmers a non-negative but stochastic amount that was decoupled from farmers' agricultural activities. A rich panel data set spanning from 2008 to 2013 enables us to control for self-selection into the program and to study its impact on small-scale rice farmers in relatively poor Northeastern Thailand. Program participation increases rice production but also leads to shifts in the composition of income generating activities away from agriculture, which may be beneficial for rural development. Decreasing risk-aversion and relieved credit constraints may be possible channels for these effects.
Keywords: D13; H25; I38; Q12; 330; Cash transfers; Agricultural subsidies; Farm households; Thailand; Propensity score matching